High-elasticity skin-friendly thermal fabric and preparation method thereof

By modifying nanozirconium carbide and graphene oxide into functional composite materials, combined with modified cotton fibers, spandex fibers and nylon fibers, it uses vortex spinning technology to woven into a highly elastic and skin-friendly and warm fabric, which solves the problem of poor fabric performance in the prior art, and achieves fabric performance with high elasticity, good warmth, excellent hygroscopicity and skin-friendly degree.

CN119553417APending Publication Date: 2025-03-04常熟市金鹅纺织科技有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411796726.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to achieve excellent fabric performance in terms of warmth, elasticity and skin-friendliness. Traditional fabrics have problems such as slab bonding, agglomeration, odor, insect worm damaging and mildew.

Method used

By modifying nanozirconium carbide and graphene oxide, a functional composite material is formed, and combined with modified cotton fibers, spandex fibers and nylon fibers, it is woven into a highly elastic, skin-friendly and warm fabric using vortex spinning process.

Benefits of technology

It achieves high elasticity, good warmth, excellent hygroscopicity and skin-friendliness, while improving the strength, softness and antibacterial properties of the fabric, avoiding agglomeration and odor problems.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of fabrics and preparation thereof, and discloses a high-elasticity skin-friendly warm-keeping fabric and a preparation method thereof.Spandex fibers are used as core yarns, polyamide fibers are used as outer cladding layers, covering yarns are woven through a vortex spinning technology, the covering yarns are used as warp yarns, functional cotton fibers are woven into weft yarns, and the high-elasticity skin-friendly warm-keeping fabric is prepared. The functional composite material is obtained through reaction of epoxidized zirconium carbide and aminated graphene, and the fabric has the advantages of being good in moisture retention, warm to wear, free of stimulation to the human body, high in elasticity, good in moisture absorption, skin-friendly, soft, capable of achieving the heat storage effect and excellent in warm keeping effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics and preparation thereof, in particular to a high-elasticity skin-friendly warm-keeping fabric and a preparation method thereof. Background Art

[0002] With the continuous development of society, people have higher and higher requirements for the performance of clothing fabrics, especially in terms of warmth, elasticity and skin-friendliness. Traditional skin-friendly thermal fabrics are generally made of cotton fibers, wool, etc., which have good air permeability and moisture absorption, can keep the skin dry, reduce friction and discomfort, and usually adopt a thickened design with excellent warmth retention, but there is a defect that the clothes are too thick and bloated. Cotton fibers are prone to problems such as hardening and agglomeration after long-term use. After deformation under the action of external force, their ability to restore their original shape is relatively weak. Thermal fabrics made of wool have excellent elasticity, but have a certain odor. They are prone to insect infestation and mildew after long-term storage, which seriously affects the warmth retention and use experience.

[0003] High elastic fabrics are usually made of elastic fibers such as spandex and polyester fibers. These fibers have excellent stretch and resilience, allowing the fabrics to adapt to various movements of the human body and provide a comfortable wearing experience, but pure elastic fiber fabrics have poor thermal insulation performance. Chinese patent application CN104005134A discloses a method for preparing acrylic blended yarns and underwear products. The acrylic blended yarns include acrylic fibers, regenerated cellulose fibers, and spandex fibers. After a weaving process, underwear fabrics are obtained. The fabrics have good thermal insulation and elasticity, but the hygroscopicity of the fabrics is poor, and it is easy to get stuffy and breed bacteria.

[0004] Therefore, it is particularly important to develop a fabric with high elasticity, skin-friendliness and excellent warmth retention. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the deficiencies in the prior art, the present invention provides a high-elasticity skin-friendly thermal insulation fabric and a preparation method thereof, and prepares a skin-friendly fabric with high elasticity and good thermal insulation effect.

[0007] (II) Technical solution

[0008] In order to achieve the above object, the present invention discloses a method for preparing a highly elastic skin-friendly warm-keeping fabric, comprising the following steps:

[0009] Step 1: Evenly mix the ethanol solution and γ-glycidyloxypropyltrimethoxysilane, adjust the pH value to 4 with acetic acid, add nano zirconium carbide, disperse by ultrasonic, react, filter after the reaction, wash with anhydrous ethanol and deionized water until neutral, and vacuum dry at 60° C. for 24 hours to obtain epoxidized zirconium carbide;

[0010] Step 2: ultrasonically disperse graphene oxide in N,N-dimethylformamide, and after uniform dispersion, add triethylenetetramine and dicyclohexylcarbocyanine (DCC), stir and mix, react, and after the reaction is completed, filter, wash with anhydrous ethanol and deionized water, and vacuum dry at 60° C. for 12 hours to obtain amino graphene;

[0011] Step 3: Ultrasonic dispersion of epoxidized zirconium carbide and amino graphene in anhydrous ethanol, heating under reflux in a nitrogen atmosphere, stirring, reacting, filtering after the reaction, washing with anhydrous ethanol, and vacuum drying at 60° C. for 24 h to obtain a functional composite material;

[0012] Step 4: Treat the cotton fiber with alkali solution. After the treatment, wash it with deionized water until it is neutral to obtain the treated cotton fiber. Mix the deionized water, functional composite material, softener and dispersant evenly to obtain a modified liquid. Dip the treated cotton fiber into the modified liquid at a temperature of 45-55°C for 40-55 minutes. After the dipping is completed, dry it at 50°C to obtain the functional cotton fiber.

[0013] Step 5: Use spandex fiber as the core yarn and nylon fiber as the outer layer, adopt vortex spinning technology to weave core-spun yarn, use the core-spun yarn as the warp yarn, and use functional cotton fiber to weave the weft yarn. The warp and weft yarns are woven through a large circular machine to obtain a highly elastic, skin-friendly and warm fabric.

[0014] Preferably, in step 1, the mass ratio of nano zirconium carbide, ethanol solution and γ-glycidyloxypropyltrimethoxysilane is 100:6000-7500:50-70.

[0015] Preferably, the reaction temperature in step 1 is 60-70°C and the reaction time is 12-18h.

[0016] Preferably, the ethanol solution in step 1 is a 50% ethanol aqueous solution.

[0017] Preferably, in the step 2, the mass ratio of graphene oxide, N,N-dimethylformamide, triethylenetetramine and dicyclohexylcarboximide is 100:8200-9000:300-350:45-60.

[0018] Preferably, the reaction temperature in step 2 is 105-115°C and the reaction time is 24-30h.

[0019] Preferably, in step three, the mass ratio of epoxidized zirconium carbide, amino graphene and anhydrous ethanol is 100:55-80:4500-6000.

[0020] Preferably, the reaction temperature in step 3 is 70-80°C and the reaction time is 8-10h.

[0021] Preferably, in the alkali treatment of the cotton fiber in step 4, the alkali solution used is a sodium hydroxide solution, the sodium hydroxide solution is a sodium hydroxide aqueous solution with a concentration of 0.5 mol / L, and the treatment temperature is 105°C and the treatment time is 2h.

[0022] Preferably, the modified liquid in step 4 is composed of deionized water, functional composite material, softener and dispersant in a mass ratio of 100:3-8:0.5-0.8:0.1-0.3.

[0023] Preferably, the softener in step 4 is bis-amino-terminated polydimethylsiloxane.

[0024] Preferably, the dispersant in step 4 is vinyl bisstearamide.

[0025] Preferably, the mass ratio of the treated cotton fiber to the modified liquid in step 4 is 100:950-1500.

[0026] Preferably, in step five, the mass ratio of spandex fiber to nylon fiber is 100:142-150.

[0027] Preferably, in step 5, the imperial count of the warp yarn is 40-50S, and the imperial count of the weft yarn is 35-42S.

[0028] Preferably, in step five, the warp yarn density is 110-128 yarns / inch, and the weft yarn density is 68-78 yarns / inch.

[0029] A high-elasticity, skin-friendly and warm-keeping fabric prepared by adopting the method for preparing the high-elasticity, skin-friendly and warm-keeping fabric.

[0030] (III) Beneficial technical effects

[0031] In the present invention, γ-glycidyloxypropyltrimethoxysilane is used to modify nano zirconium carbide, epoxy groups are introduced on the surface of nano zirconium carbide, triethylenetetramine is used to modify graphene oxide, carboxyl groups on the surface of graphene oxide and amino groups on triethylenetetramine undergo amidation reaction to obtain amino graphene, and a large number of amino and imine groups are introduced on graphene. Epoxy ring-opening reaction occurs between epoxidized zirconium carbide and amino graphene to obtain a functional composite material. Deionized water, functional composite material, softener and dispersant are mixed evenly to obtain a modified liquid, and cotton fiber treated with alkali solution is impregnated and modified to obtain functional cotton fiber. Spandex fiber is used as core yarn and nylon fiber as outer cladding, and core-spun yarn is woven into warp yarn by vortex spinning process, and the core-spun yarn is used as warp yarn, and functional cotton fiber is woven into weft yarn, and the warp yarn and weft yarn are woven through a large circular knitting machine for warp and weft weaving to obtain a highly elastic skin-friendly warm fabric.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The nano zirconium carbide used in the present invention can absorb the energy of near-infrared rays with a wavelength less than 2.0 μm and convert it into heat energy. At the same time, it can reflect the heat radiation emitted by the human body to a large extent, has excellent heat storage and heat absorption capabilities, and has a good warming effect. Graphene oxide can absorb the far-infrared energy released by the human body and reflect it back to the human body, forming a cyclical warming effect. At the same time, graphene oxide has excellent mechanical properties, good flexibility and efficient thermal conductivity. Adding it to the fiber can increase the force between the fibers, significantly improve the strength and elasticity of the fabric, and at the same time improve the softness and comfort of the fabric. Further, graphene oxide also has excellent antibacterial properties and can effectively inhibit bacterial growth. Nano zirconium carbide and graphene oxide have strong water absorption capacity and can quickly absorb moisture and sweat secreted by the human body. After the two react, they effectively avoid agglomeration and can be evenly dispersed in the cotton fiber. A large number of hydrophilic groups such as amino, imine, and hydroxyl groups are introduced into the functional composite material, which can further provide a moist feeling and skin affinity.

[0034] (2) The spandex fiber in the present invention has high elasticity and good adaptability to the human body, and is suitable for close-fitting fabrics, but its hygroscopicity is poor and the hygroscopicity range is small. Nylon fiber has a small initial modulus, a high regain, and a high thermal conductivity. Nylon fabrics have the characteristics of soft hand feel and good skin-friendly performance. At the same time, they contain a large number of hydrophilic functional groups, have excellent thermal conductivity, good hygroscopicity, and excellent quick-drying properties. Using spandex fiber as the core yarn and nylon fiber as the outer layer to make core-spun yarn can effectively improve the shortcomings of spandex fiber. Cotton fiber has good hygroscopicity and air permeability, can absorb moisture in the air, and makes people feel soft and not stiff when it comes into contact with the skin. It has excellent heat resistance, is soft and not stiff, makes people feel comfortable, and has good moisture retention, is warm to wear, and has no irritation to the human body. After modification, its elasticity is greatly improved. A large number of active functional groups on the core-spun yarn and functional cotton fiber are easy to generate intermolecular forces, and the forces between them are strong. The fabric obtained after warp and weft weaving on a large circular machine has the characteristics of high elasticity, good moisture absorption, skin-friendly and soft, can store heat, and has excellent warmth retention effect. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] A method for preparing a highly elastic skin-friendly thermal insulation fabric comprises the following steps:

[0038] Step 1, the ethanol solution and γ-glycidyloxypropyltrimethoxysilane are mixed evenly, the pH value is adjusted to 4 with acetic acid, and then nano zirconium carbide is added, and ultrasonic dispersion is performed, wherein the mass ratio of nano zirconium carbide, ethanol solution, and γ-glycidyloxypropyltrimethoxysilane is 100:6000:50, the ethanol solution is 50% ethanol aqueous solution, and the reaction is carried out at 60° C. The reaction time is 18 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water until neutral, and vacuum dried at 60° C. for 24 hours to obtain epoxidized zirconium carbide;

[0039] Step 2, ultrasonically disperse graphene oxide in N, N-dimethylformamide, and after uniform dispersion, add triethylenetetramine and dicyclohexylcarboximide, stir and mix, wherein the mass ratio of graphene oxide, N, N-dimethylformamide, triethylenetetramine and dicyclohexylcarboximide is 100:8200:300:45, react at 105°C, and the reaction time is 30h. After the reaction is completed, filter, wash with anhydrous ethanol and deionized water, and vacuum dry at 60°C for 12h to obtain amino graphene;

[0040] Step 3, ultrasonically dispersing the epoxidized zirconium carbide and the amino graphene in anhydrous ethanol, wherein the mass ratio of the epoxidized zirconium carbide, the amino graphene, and the anhydrous ethanol is 100:55:4500, heating under reflux in a nitrogen atmosphere, stirring, reacting at 70°C for 10 hours, filtering after the reaction, washing with anhydrous ethanol, and vacuum drying at 60°C for 24 hours to obtain a functional composite material;

[0041] Step 4: Treat the cotton fiber with alkali solution. After the treatment, wash it with deionized water until it is neutral to obtain the treated cotton fiber. Mix deionized water, functional composite material, softener diamino-terminated polydimethylsiloxane and dispersant vinyl bisstearamide in a mass ratio of 100:3:0.5:0.1 to obtain a modified solution. Immerse the treated cotton fiber in the modified solution. The mass ratio of the treated cotton fiber to the modified solution is 100:950. The immersion temperature is 45°C and the immersion time is 55min. After the immersion is completed, dry it at 50°C to obtain functional cotton fiber.

[0042] Step 5. Use spandex fiber as the core yarn and nylon fiber as the outer covering, wherein the mass ratio of spandex fiber to nylon fiber is 100:142, and adopt vortex spinning process to weave core-spun yarn, the core-spun yarn is used as warp yarn, and functional cotton fiber is spun into weft yarn. The warp yarn and weft yarn are woven through a large circular machine. The imperial count of the warp yarn is 40S, the imperial count of the weft yarn is 35S, the warp yarn density is 110 strands / inch, and the weft yarn density is 68 strands / inch, so as to obtain a highly elastic, skin-friendly and warm fabric.

[0043] Example 2

[0044] A method for preparing a highly elastic skin-friendly thermal insulation fabric comprises the following steps:

[0045] Step 1, the ethanol solution and γ-glycidyloxypropyltrimethoxysilane are mixed evenly, the pH value is adjusted to 4 with acetic acid, and then nano zirconium carbide is added, and ultrasonic dispersion is performed, wherein the mass ratio of nano zirconium carbide, ethanol solution, and γ-glycidyloxypropyltrimethoxysilane is 100:7000:60, the ethanol solution is 50% ethanol aqueous solution, and the reaction is carried out at 65° C. The reaction time is 15 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water until neutral, and vacuum dried at 60° C. for 24 hours to obtain epoxidized zirconium carbide;

[0046] Step 2, ultrasonically disperse graphene oxide in N, N-dimethylformamide, after uniform dispersion, add triethylenetetramine and dicyclohexylcarboximide, stir and mix, wherein the mass ratio of graphene oxide, N, N-dimethylformamide, triethylenetetramine and dicyclohexylcarboximide is 100:8600:320:55, react at 110°C, the reaction time is 26h, after the reaction is completed, filter, wash with anhydrous ethanol and deionized water, and vacuum dry at 60°C for 12h to obtain amino graphene;

[0047] Step 3, ultrasonically dispersing the epoxidized zirconium carbide and the amino graphene in anhydrous ethanol, wherein the mass ratio of the epoxidized zirconium carbide, the amino graphene, and the anhydrous ethanol is 100:68:5200, heating under reflux in a nitrogen atmosphere, stirring, reacting at 75°C for 9 hours, filtering after the reaction, washing with anhydrous ethanol, and vacuum drying at 60°C for 24 hours to obtain a functional composite material;

[0048] Step 4, using alkali solution to treat the cotton fiber, after the treatment is completed, washing with deionized water to neutrality to obtain the treated cotton fiber, deionized water, functional composite material, softener diamino-terminated polydimethylsiloxane and dispersant vinyl bisstearamide in a mass ratio of 100:5:0.6:0.2 are mixed evenly to obtain a modified liquid, and the treated cotton fiber is immersed in the modified liquid. The mass ratio of the treated cotton fiber and the modified liquid is 100:1200, the immersion temperature is 50, and the immersion time is 50min. After the immersion is completed, it is dried at 50°C to obtain functional cotton fiber;

[0049] Step 5. Use spandex fiber as the core yarn and nylon fiber as the outer layer, wherein the mass ratio of spandex fiber to nylon fiber is 100:148, and adopt vortex spinning process to weave core-spun yarn, the core-spun yarn is used as warp yarn, and functional cotton fiber is spun into weft yarn. The warp yarn and weft yarn are woven through a large circular machine. The imperial count of the warp yarn is 45S, the imperial count of the weft yarn is 38S, the warp yarn density is 115 strands / inch, and the weft yarn density is 70 strands / inch, so as to obtain a highly elastic, skin-friendly and warm fabric.

[0050] Example 3

[0051] A method for preparing a highly elastic skin-friendly thermal insulation fabric comprises the following steps:

[0052] Step 1, using alkali solution to treat cotton fiber, after the treatment is completed, using deionized water to wash to neutrality to obtain treated cotton fiber, deionized water, functional composite material, softener diamino-terminated polydimethylsiloxane and dispersant vinyl bisstearamide in a mass ratio of 100:7:0.6:0.2 are mixed evenly to obtain a modified liquid, and the treated cotton fiber is immersed in the modified liquid. The mass ratio of the treated cotton fiber and the modified liquid is 100:1200, the immersion temperature is 50, the immersion time is 50min, and after the immersion is completed, it is dried at 50°C to obtain functional cotton fiber;

[0053] Step 2: Use spandex fiber as the core yarn and nylon fiber as the outer covering, wherein the mass ratio of spandex fiber to nylon fiber is 100:148, and adopt vortex spinning process to weave core-spun yarn, the core-spun yarn is used as the warp yarn, and the functional cotton fiber is spun into the weft yarn. The warp yarn and the weft yarn are woven through a large circular machine for warp and weft weaving. The imperial count of the warp yarn is 48S, the imperial count of the weft yarn is 40S, the warp yarn density is 125 strands / inch, and the weft yarn density is 75 strands / inch, so as to obtain a highly elastic, skin-friendly and warm fabric.

[0054] The preparation method of the functional composite material is the same as the preparation method of the functional composite material in Example 2.

[0055] Example 4

[0056] A method for preparing a highly elastic skin-friendly thermal insulation fabric comprises the following steps:

[0057] Step 1, the ethanol solution and γ-glycidyloxypropyltrimethoxysilane are mixed evenly, the pH value is adjusted to 4 with acetic acid, and then nano zirconium carbide is added, and ultrasonic dispersion is performed, wherein the mass ratio of nano zirconium carbide, ethanol solution, and γ-glycidyloxypropyltrimethoxysilane is 100:7500:70, the ethanol solution is a 50% ethanol aqueous solution, and the reaction is carried out at 70° C. The reaction time is 12 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water until neutral, and vacuum dried at 60° C. for 24 hours to obtain epoxidized zirconium carbide;

[0058] Step 2, ultrasonically disperse graphene oxide in N,N-dimethylformamide, after uniform dispersion, add triethylenetetramine and dicyclohexylcarboximide, stir and mix, wherein the mass ratio of graphene oxide, N,N-dimethylformamide, triethylenetetramine and dicyclohexylcarboximide is 100:9000:350:60, react at 115°C, the reaction time is 24h, after the reaction is completed, filter, wash with anhydrous ethanol and deionized water, and vacuum dry at 60°C for 12h to obtain amino graphene;

[0059] Step 3, ultrasonically dispersing the epoxidized zirconium carbide and the amino graphene in anhydrous ethanol, wherein the mass ratio of the epoxidized zirconium carbide, the amino graphene, and the anhydrous ethanol is 100:80:6000, heating under reflux in a nitrogen atmosphere, stirring, reacting at 80°C for 8 hours, filtering after the reaction, washing with anhydrous ethanol, and vacuum drying at 60°C for 24 hours to obtain a functional composite material;

[0060] Step 4: Treat the cotton fiber with alkali solution. After the treatment, wash it with deionized water until it is neutral to obtain the treated cotton fiber. Mix deionized water, functional composite material, softener diamino-terminated polydimethylsiloxane and dispersant vinyl bisstearamide in a mass ratio of 100:8:0.8:0.3 to obtain a modified solution. Immerse the treated cotton fiber in the modified solution. The mass ratio of the treated cotton fiber to the modified solution is 100:1500. The immersion temperature is 55°C and the immersion time is 40min. After the immersion is completed, dry it at 50°C to obtain functional cotton fiber.

[0061] Step 5. Use spandex fiber as the core yarn and nylon fiber as the outer covering, wherein the mass ratio of spandex fiber to nylon fiber is 100:150, and adopt vortex spinning process to weave core-spun yarn, the core-spun yarn is used as warp yarn, and functional cotton fiber is spun into weft yarn. The warp yarn and weft yarn are woven through a large circular machine. The imperial count of the warp yarn is 50S, the imperial count of the weft yarn is 42S, the warp yarn density is 128 strands / inch, and the weft yarn density is 78 strands / inch, so as to obtain a highly elastic, skin-friendly and warm fabric.

[0062] Comparative Example 1

[0063] A method for preparing a functional fabric comprises the following steps:

[0064] Step 1, the ethanol solution and γ-glycidyloxypropyltrimethoxysilane are mixed evenly, the pH value is adjusted to 4 with acetic acid, and then nano zirconium carbide is added, and ultrasonic dispersion is performed, wherein the mass ratio of nano zirconium carbide, ethanol solution, and γ-glycidyloxypropyltrimethoxysilane is 100:7000:60, the ethanol solution is 50% ethanol aqueous solution, and the reaction is carried out at 65° C. The reaction time is 15 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water until neutral, and vacuum dried at 60° C. for 24 hours to obtain epoxidized zirconium carbide;

[0065] Step 2, ultrasonically disperse graphene oxide in N, N-dimethylformamide, after uniform dispersion, add triethylenetetramine and dicyclohexylcarboximide, stir and mix, wherein the mass ratio of graphene oxide, N, N-dimethylformamide, triethylenetetramine and dicyclohexylcarboximide is 100:8600:320:55, react at 110°C, the reaction time is 26h, after the reaction is completed, filter, wash with anhydrous ethanol and deionized water, and vacuum dry at 60°C for 12h to obtain amino graphene;

[0066] Step 3, using alkali solution to treat the cotton fiber, after the treatment is completed, washing with deionized water to neutrality to obtain the treated cotton fiber, deionized water, epoxidized zirconium carbide, amino graphene, softener bisamino-terminated polydimethylsiloxane and dispersant vinyl bisstearamide in a mass ratio of 100:4.2:2.8:0.6:0.2 are mixed evenly to obtain a modified solution, and the treated cotton fiber is immersed in the modified solution. The mass ratio of the treated cotton fiber and the modified solution is 100:1200, the immersion temperature is 50, the immersion time is 50min, and after the immersion is completed, it is dried at 50°C to obtain a modified cotton fiber;

[0067] Step 4: Use spandex fiber as the core yarn and nylon fiber as the outer covering, wherein the mass ratio of spandex fiber to nylon fiber is 100:148, adopt vortex spinning process to weave core-spun yarn, the core-spun yarn is used as warp yarn, and modified cotton fiber is spun into weft yarn. The warp yarn and weft yarn are woven through a large circular machine. The imperial count of the warp yarn is 48S, the imperial count of the weft yarn is 40S, the warp yarn density is 125 strands / inch, and the weft yarn density is 75 strands / inch, so as to obtain a functional fabric.

[0068] Comparative Example 2

[0069] A method for preparing a functional fabric comprises the following steps:

[0070] Step 1, using alkali solution to treat cotton fiber, after the treatment is completed, using deionized water to wash to neutrality to obtain treated cotton fiber, deionized water, nano zirconium carbide, graphene oxide, softener bisamino-terminated polydimethylsiloxane and dispersant vinyl bisstearamide in a mass ratio of 100:4.2:2.8:0.6:0.2 are mixed evenly to obtain a modified solution, and the treated cotton fiber is immersed in the modified solution. The mass ratio of the treated cotton fiber and the modified solution is 100:1200, the immersion temperature is 50, and the immersion time is 50min. After the immersion is completed, it is dried at 50°C to obtain modified cotton fiber;

[0071] Step 2: Use spandex fiber as the core yarn and nylon fiber as the outer covering, wherein the mass ratio of spandex fiber to nylon fiber is 100:148, adopt vortex spinning process to weave into core-spun yarn, the core-spun yarn is used as warp yarn, and modified cotton fiber is spun into weft yarn. The warp yarn and weft yarn are woven through a large circular machine, the imperial count of the warp yarn is 48S, the imperial count of the weft yarn is 40S, the warp yarn density is 125 strands / inch, and the weft yarn density is 75 strands / inch, to obtain a functional fabric.

[0072] In the above-mentioned embodiments and comparative examples, in the process of using alkali solution to treat cotton fibers, the alkali solution used is sodium hydroxide solution, and the sodium hydroxide solution is a sodium hydroxide aqueous solution with a concentration of 0.5 mol / L. During the treatment process, the treatment temperature is 105°C and the treatment time is 2h.

[0073] The nano zirconium carbide used in the embodiments and comparative examples of the present invention is nano zirconium carbide powder, purchased from Hefei Kaier Nano Technology Development Co., Ltd., with an average particle size of less than 50nm and a purity of greater than 99.0%; the graphene oxide is multilayer graphene oxide, purchased from Suzhou Hengqiu Technology Co., Ltd. (purity>95wt%, thickness of 3.4-8nm, and sheet diameter of 10-50μm); the spandex fiber is purchased from Jiangsu Qiaoxin Fiber Co., Ltd., specifically 1680D spandex yarn; the cotton fiber is Xinjiang long-staple cotton with a fiber length of 38-39.7mm; the nylon fiber is single-hole hollow, with a brand name of 28T 12-2H9B and a linear density of 2.8tex / 12F, purchased from Toray Industries, Ltd. of Japan; all raw materials used without other instructions are commercially available raw materials.

[0074] Corresponding tests were performed on the fabrics prepared in Examples 1-4 and Comparative Examples 1-2. The test methods and test results are as follows:

[0075] (1) Thermal insulation performance test: Under simulated sunlight, the illumination is 600Cal / m 2 hr, the initial temperature is 5, °C and the humidity is 60% RH, and the temperature difference of the fabrics obtained in Examples 1-4 and Comparative Examples 1-2 is tested after 30 minutes;

[0076] (2) Comfort test: Test the softness of the fabric using the AATCC202 standard;

[0077] The above test results are shown in Table 1:

[0078] Table 1

[0079] Test items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 30min temperature difference (℃) 5.8 6.5 6.8 6.2 5.1 4.6 Softness Soft and not hard - - - - Softer

[0080] “-” means “soft and not hard”.

[0081] According to the test results in Table 1, it can be seen that the corresponding fabrics in Examples 1-4 have excellent thermal insulation performance, show good softness, good comfort, and are soft and not hard. The 30-minute temperature difference of the corresponding fabric in Example 3 can reach 6.8°C. In Comparative Example 2, the nano zirconium carbide and graphene oxide were not modified, and the dispersibility and compatibility were greatly reduced, the heat storage performance was greatly reduced, the thermal insulation was deteriorated, and the comfort was deteriorated.

[0082] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a highly elastic skin-friendly warm fabric, characterized in that: The steps include: Step 1: Evenly mix the ethanol solution and γ-glycidyloxypropyltrimethoxysilane, adjust the pH value to 4, add nano zirconium carbide, disperse by ultrasonic, react, and after the reaction is completed, filter, wash, and vacuum dry at 60° C. for 24 hours to obtain epoxidized zirconium carbide; Step 2: Ultrasonically disperse graphene oxide in N,N-dimethylformamide, and after uniform dispersion, add triethylenetetramine and dicyclohexylcarboximide, stir and mix, and react. After the reaction is completed, filter, wash, and vacuum dry at 60° C. for 12 hours to obtain amino graphene; Step 3, ultrasonically dispersing the epoxidized zirconium carbide and amino graphene in anhydrous ethanol, heating under reflux, stirring, and reacting in a nitrogen atmosphere, filtering, washing, and vacuum drying at 60° C. for 24 hours after the reaction is completed to obtain a functional composite material; Step 4: Treat the cotton fiber with alkali solution. After the treatment, wash it with deionized water until it is neutral to obtain the treated cotton fiber. Mix the deionized water, functional composite material, softener and dispersant evenly to obtain a modified liquid. Dip the treated cotton fiber into the modified liquid at a temperature of 45-55°C for 40-55 minutes. After the dipping is completed, dry it at 50°C to obtain the functional cotton fiber. Step 5: Use spandex fiber as the core yarn and nylon fiber as the outer layer, adopt vortex spinning technology to weave core-spun yarn, use the core-spun yarn as warp yarn, and weave functional cotton fiber into weft yarn. The warp yarn and weft yarn are woven through a large circular machine to obtain a highly elastic, skin-friendly and warm fabric.

2. The method for preparing a highly elastic skin-friendly warm-keeping fabric according to claim 1, characterized in that: In the step 1, the mass ratio of nano zirconium carbide, ethanol solution and γ-glycidyloxypropyltrimethoxysilane is 100:6000-7500:50-70, the reaction temperature is 60-70°C, and the reaction time is 12-18h.

3. The method for preparing a highly elastic skin-friendly warm-keeping fabric according to claim 1, characterized in that: In the step 2, the mass ratio of graphene oxide, N,N-dimethylformamide, triethylenetetramine and dicyclohexylcarboximide is 100:8200-9000:300-350:45-60, the reaction temperature is 105-115°C, and the reaction time is 24-30h.

4. The method for preparing a highly elastic skin-friendly warm-keeping fabric according to claim 1, characterized in that: In the step three, the mass ratio of epoxidized zirconium carbide, amino graphene and anhydrous ethanol is 100:55-80:4500-6000.

5. The method for preparing a highly elastic skin-friendly warm-keeping fabric according to claim 1, characterized in that: The reaction temperature in step 3 is 70-80°C and the reaction time is 8-10h.

6. The method for preparing a highly elastic skin-friendly warm-keeping fabric according to claim 1, characterized in that: The modified liquid in step 4 is composed of deionized water, functional composite material, softener and dispersant in a mass ratio of 100:3-8:0.5-0.8:0.1-0.

3.

7. The method for preparing a highly elastic skin-friendly warm-keeping fabric according to claim 1, characterized in that: The mass ratio of the treated cotton fiber to the modified liquid in the step 4 is 100:950-1500.

8. The method for preparing a highly elastic skin-friendly warm-keeping fabric according to claim 1, characterized in that: In the step 5, the mass ratio of spandex fiber to nylon fiber is 100:142-150.

9. The method for preparing a highly elastic skin-friendly warm-keeping fabric according to claim 1, characterized in that: In the step 5, the imperial count of the warp yarn is 40-50S, the imperial count of the weft yarn is 35-42S, the warp yarn density is 110-128 yarns / inch, and the weft yarn density is 68-78 yarns / inch.

10. A highly elastic skin-friendly thermal insulation fabric prepared by the method for preparing a highly elastic skin-friendly thermal insulation fabric as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing warm and intelligent acrylic fiber blended yarn and underwear product

    CN104005134A

  • Method for modifying epoxy resin through amino-terminated hyperbranched polymer-grafted graphene oxide

    CN102504147A

  • Method capable of enhancing hydrophilic performance of cotton fibers

    CN111485427A

  • High-strength heat-resistant polyethylene material and preparation method thereof

    CN113956560A

  • Thermal-storage warm-keeping acrylic fiber blended yarn, preparation method thereof and application of thermal-storage warm-keeping acrylic fiber blended yarn in underwear fabric

    CN116397358A